Investigating Income Inequality Dynamics in the United States - Islam, T M Tonmoy (Journal of Income Distribution®, 2017)
Recently, income inequality has been rising in many parts of the world. This is creating some serious concerns among policymakers, as higher levels of income inequality can lead to various social ills. However, little is known about the role of historical factors in explaining the current level of inequality. I use the model of Durlauf (1996) as reference to create an econometric model to estimate this impact. Using current and historical data of US states, I find that illiteracy rate in 1920 has a strong positive influence on current level of inequality. The simulation results show that eliminating illiteracy in 1920 would have reduced contemporaneous inequality by 1-5 percent. Higher illiteracy indicates a lower level of human capital, and that can affect income distribution. Through the intergenerational transmission of income, this income distribution is exacerbated in the future, leading to higher levels of inequality.